PENGARUH KEPERCAYAAN DIRI TERHADAP KEMAMPUAN PUBLIC SPEAKING SISWA DI SMA N 1 MUARO JAMBI - Dewi Sulastri; Rasimin Rasimin; Affan Yusra (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
The ability to speak in public is a very important skill in various aspects of life, including aspects of education, career and social interaction. For students, the ability to speak in public can help in effective communication, express ideas or thoughts clearly, and of course strengthen their sense of self-confidence. Students who are able to overcome anxiety and maintain public speaking skills can be said to have high self-confidence. The aim of this research was to measure the influence of self-confidence on public speaking abilities in students at SMA N 1 Muaro Jambi with a sample size of 118 students. The research method is quantitative, expost-facto approach, sampling using purposive sampling through questionnaires or questionnaires as a data collection tool. The research results show that self-confidence (X) has an influence on public speaking ability (Y), with a determination value of 0.437 or 43.7%, which is quite strong.